ANALYSIS OF HOSPITALIZATIONS AT THE INTERNAL MEDICINE UNIT, IMPACT OF DIABETES MELLITUS - Pablo Ferrada (Revista de la Sociedad Argentina de Diabetes, 2018)
Introduction: one in four patients admitted to a hospital has a previous diagnosis of diabetes (DM), with hospital readmissions being frequent in the same year. The hospitalization can be related to a complication of the DM or more commonly with another pathology. Objectives: to determine in patients hospitalized in the Medical Clinic Service (CM) of the Hospital General de Agudos of the third level of complexity of Mendoza: prevalence of DM, causes of hospitalization, hospital stay, previous hospitalizations and re-admissions, mortality, and a comparison between patients with or without DM (DM, non-DM respectively).